The possibility of revision of a judgement in civil proceedings on the basis of a ruling made by an international body – de lege ferenda conclusions - Flegel, Aleksandra (The Opole Studies in Administration and Law, 2021)
This article aims to indicate the need for amending the Code of Civil Procedure to the extent that the civil procedure does not provide the possibility of revision of a judgment in civil proceedings on the basis of a ruling made by an international body. Such a conclusion results from the analysis of the currently applicable regulations on the possibility of reopening civil proceedings against the background of similar regulations concerning administrative court proceedings and criminal proceedings, taking into account the validity of EU regulations. The whole issue will be presented against the background of fundamental principles governing the legal system as such.